Evidence in vivo that the DEAD-box RNA helicase RhlB facilitates the degradation of ribosome-free mRNA by RNase E - Khemici, Vanessa (National Academy of Sciences, 2005)
The RNA degradosome of Escherichia coli is a ribonucleolytic multienzyme complex containing RNase E, polynucleotide phosphorylase, RhlB, and enolase. Previous in vitro and in vivo work has shown that RhlB facilitates the exonucleolytic degradation of structured mRNA decay intermediates by polynucleotide phosphorylase in an ATPase-dependent reaction. Here, we show that deleting the gene encoding RhlB stabilizes a lacZ mRNA transcribed by bacteriophage T7 RNA polymerase. Deleting the gene encoding enolase has little if any effect. Other messages transcribed by T7 polymerase are also stabilized by ΔrhlB. The effect of point mutations inactivating RhlB is comparable with the effect of deleting the gene. Primer extension analysis of the lacZ message indicates that RhlB facilitates endoribonucleolytic cleavage by RNase E, demonstrating a functional interaction between the RNA helicase and the endoribonuclease. The possible physiological role of an RhlB-RNase E pathway and the mechanisms by which RhlB could facilitate RNase E cleavage are discussed.